THE EXISTENCE OF SINOM HOUSE IN BENDOSARI, KADEMANGAN, BLITAR IN TERMS OF SPACE CONFIGURATION - Wirawan, Yosua Bagus; Wahjutami, Erlina Laksmiani; Bonifacius, Nurhamdoko (Border: Jurnal Arsitektur, 2024)
Traditional houses are important to maintain and explore because the values of wisdom are embedded in them. Sinom House is an architectural manifestation of Javanese people's homes with the characteristic of a pyramid roof shape; in general, Sinom houses can be found in Java. In this study, the object of the Sinom house studied was in Bendosari Village, Kademangan, Blitar, which has the character of a rural area with a rocky mountainous landscape that tends to have hot weather, as well as the characteristics of a community working in agriculture, from these factors resulting in a simpler Sinom house shape in terms of area and spatial configuration. This study aims to identify the characteristics of the existence of the spatial configuration of the Sinom house in the location of Bendosari Village, Kademangan District, where the factors to be identified come from comparative literature sources, namely aspects of floor plan typology, spatial composition, roof shape and structure, and a general description of the research location. As a traditional vernacular residence of the Javanese people, these characteristics can be reviewed from the aspect of the spatial configuration that forms a single unit of the Sinom house. In the aspect of spatial configuration, the variables studied are floor plan typology, spatial composition, and roof structure. The method used in this study is descriptive qualitative in both stages of data collection and analysis. Data collection is done by direct observation, architectural documentation, and interviews as supporting data. The results of this study are expected to deepen the knowledge of Javanese residential architecture in rural areas and can be useful for enriching architectural knowledge and further research.